Improvement of Transmembrane Transport Mechanism Study of Imperatorin on P-Glycoprotein-Mediated Drug Transport - Zheng-Gen Liao; Tao Tang; Xue-Jing Guan; Wei Dong; Jing Zhang; Guo-Wei Zhao; Ming Yang; Xin-Li Liang (Molecules, 2016)
P-glycoprotein (P-gp) affects the transport of many drugs; including puerarin and vincristine. Our previous study demonstrated that imperatorin increased the intestinal absorption of puerarin and vincristine by inhibiting P-gp-mediated drug efflux. However; the underlying mechanism was not known. The present study investigated the mechanism by which imperatorin promotes P-gp-mediated drug transport. We used molecular docking to predict the binding force between imperatorin and P-gp and the effect of imperatorin on P-gp activity. P-gp efflux activity and P-gp ATPase activity were measured using a rhodamine 123 (Rh-123) accumulation assay and a Pgp-Glo™ assay; respectively. The fluorescent probe 1,6-diphenyl-1,3,5-hexatriene (DPH) was used to assess cellular membrane fluidity in MDCK-MDR1 cells. Western blotting was used to analyze the effect of imperatorin on P-gp expression; and P-gp mRNA levels were assessed by qRT-PCR. Molecular docking results demonstrated that the binding force between imperatorin and P-gp was much weaker than the force between P-gp and verapamil (a P-gp substrate). Imperatorin activated P-gp ATPase activity; which had a role in the inhibition of P-gp activity. Imperatorin promoted Rh-123 accumulation in MDCK-MDR1 cells and decreased cellular membrane fluidity. Western blotting demonstrated that imperatorin inhibited P-gp expression; and qRT-PCR revealed that imperatorin down-regulated P-gp (MDR1) gene expression. Imperatorin decreased P-gp-mediated drug efflux by inhibiting P-gp activity and the expression of P-gp mRNA and protein. Our results suggest that imperatorin could down-regulate P-gp expression to overcome multidrug resistance in tumors.